THE NATION LOST ANOTHER GEM: CONDOLENCES FROM USM - MPRC, Pusat Media & Perhubungan Awam (2017)
PENANG, 1 March 2017 The Universiti Sains Malaysia (USM) community would like to send a message of condolence to the family of the late Tan Sri Jins Shamsudin who has passed away yesterday evening at the age of 82.